Ecology of Rumex alpinus - retrospective studies using annual growth markers on rhizomes - Šťastná, Petra (Jihočeská univerzita, 2011)
I studied the species Rumex alpinus by reviewing the literature on the taxonomy, morphology, population biology, genetics, chemistry, physiology and ecology. Herbochronological studies on growth parameters of rhizomes were done on the Rumex alpinus plants in relation to altitude and to the climtic fluctulations, specifically to the snow accumulation.
Ecology of Rumex alpinus - retrospective studies using annual growth markers on rhizomes
Keywords: Rumex alpinus; herbchronology; rhizome; altitude; snow accumulation; Nízké Tatry Mts.; Rumex alpinus; herbchronology; rhizome; altitude; snow accumulation; Nízké Tatry Mts.